2016
DOI: 10.1080/03014460.2016.1205135
|View full text |Cite
|
Sign up to set email alerts
|

The Orientalisation of North Africa: New hints from the study of autosomal STRs in an Arab population

Abstract: This study represents an additional step to obtain a comprehensive understanding of the complex demographic history of North African populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 65 publications
2
6
0
Order By: Relevance
“…This is consistent with the later date for the admixture into Halfawieen and the Arabic populations of Sudan. Previous studies [ 37 , 38 ] have found a similar pattern for populations of Maghreb, where admixture times coincide with the time of the historically documented Arab conquest.…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…This is consistent with the later date for the admixture into Halfawieen and the Arabic populations of Sudan. Previous studies [ 37 , 38 ] have found a similar pattern for populations of Maghreb, where admixture times coincide with the time of the historically documented Arab conquest.…”
Section: Resultssupporting
confidence: 69%
“…In fact most populations from northeast Sudan (Nubian, Arab and Beja groups) seem to be a mixture of Middle Eastern and local northeast African genetic components, although only the Arab groups shifted to the Semitic languages. Cultural and linguistic replacement following the Arab conquest has been described previously in populations of the Maghreb [ 37 , 38 , 43 ].…”
Section: Discussionmentioning
confidence: 91%
“…Most of Tunisian populations here analysed exhibited high levels of Y-STR diversity, reflecting the wealth of demographic histories underlying current-day populations. This finding is in agreement with previous studies using different types of markers that reported the highest genetic diversities in North African populations 17 , 37 , 38 , 43 , 62 65 . In the Tunisian population landscape, clearly conflicts the low values of diversity in the Arabs from Zriba and in the Tunisian Andalusians from Qalaat-El-Andalous.…”
Section: Discussionsupporting
confidence: 93%
“…Results revealed no statistically significant variance among groups (Table 2 ), sustaining that such common perception of ethnicity is irrelevant for the male genetic structure among Tunisian populations, as already evidenced before 12 . Yet, the variance among populations within groups was highly significant, reflecting the complexity of other factors that account for the pattern of genetic differentiation between Tunisian population 37 , 43 , 44 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation